A natural autoantibody is encoded by germline heavy and lambda light chain variable region genes without somatic mutation. - Siminovitch, K A (1989)
While nonmutated germline variable region (V) genes have been found to encode heavy or light chains of various human autoantibodies, the use of germline V genes by both chains of a given autoantibody has not been documented. Recently, we reported that the heavy chain V gene (designated Humha346) of the Kim4.6 anti-DNA antibody is identical to a germline VH gene, 1.9III. To investigate whether this autoantibody was entirely germline encoded, we searched for the germline counterpart to the Kim4.6 V lambda segment (designated Humla146) and isolated a V lambda I gene designated Humlv117, which was identical to Humla146. Together with the sequence identity of the Kim4.6/Humha346 and 1.9III VH genes, the current data provide the first direct proof that an autoantibody can be encoded entirely by germline V genes without any somatic change. In addition, Humlv117 is the first V lambda I germline gene that has been isolated, and is highly homologous to the V lambda genes expressed in two lymphomas. Thus, this V lambda I gene should provide a useful tool for investigating the expression of the human V lambda gene repertoire, particularly with regard to autoimmune and/or lymphoproliferative diseases.